Guidelines for target costing adoption in the development of products for the residential real estate market - Melo, Reymard Savio Sampaio de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2017)
This study focuses on the problems associated with the traditional practice of reducing costs in construction and the need to increase business competitiveness in the residential real estate sector. In this context, target costing is a promising approach to improve the competitiveness of companies by ensuring that the products launched on the market do not jeopardize the company's results and value delivery to customers. However, far too little attention is paid to target costing implementation by companies that develop residential real state products for sale and face strong market competition. Thus, this paper seeks to investigate whether the standard framework of target costing in the literature applies - with or without adjustments - to real estate developers. Case study was the research strategy adopted. Guidelines are proposed for the introduction of target costing in the development process of residential real estate products. The proposed guidelines are related to the three main sections of the target costing process: market-driven costing, product-level target costing and component-level target costing.